2015
DOI: 10.1111/jai.12911
|View full text |Cite
|
Sign up to set email alerts
|

Dietary valine requirement of juvenile blunt snout bream (Megalobrama amblycephalaYih, 1955)

Abstract: Summary An 8‐week feeding trial was carried out to test the hypothesis that adequate dietary valine might improve growth, feed utilization and protein content in blunt snout bream, whereas a valine deficiency might have adverse effects on these parameters. Six isonitrogenous (34% crude protein) and isoenergetic (14.2 MJ kg−1 digestible energy) experimental diets were formulated to contain graded valine levels (0.66, 0.95, 1.26, 1.55, 1.87 and 2.16% of dry weight) at about 0.30% increments replaced by equal pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 23 publications
5
12
0
Order By: Relevance
“…Previous research has established the requirement of valine as an EAA needed for protein synthesis and growth stimulation in fish (NRC, ). In this study, data for Nile tilapia fed the formulation with the lowest level of valine showed significantly lower values for WG, SGR, PER and PRE, but a higher FCR, when compared with all other treatment groups; this result is consistent with previous reports of feeding trials with mrigal carp (Ahmed & Khan, ), red sea bream (Rahimnejad & Lee, ) and blunt snout bream (Ren et al., ). The results demonstrated that the growth performance and feed utilization efficiency of juvenile Nile tilapia were significantly improved by dietary valine supplementation, suggesting that valine is an EAA for Nile tilapia whereby the juveniles are able to assimilate the valine crystal for growth.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Previous research has established the requirement of valine as an EAA needed for protein synthesis and growth stimulation in fish (NRC, ). In this study, data for Nile tilapia fed the formulation with the lowest level of valine showed significantly lower values for WG, SGR, PER and PRE, but a higher FCR, when compared with all other treatment groups; this result is consistent with previous reports of feeding trials with mrigal carp (Ahmed & Khan, ), red sea bream (Rahimnejad & Lee, ) and blunt snout bream (Ren et al., ). The results demonstrated that the growth performance and feed utilization efficiency of juvenile Nile tilapia were significantly improved by dietary valine supplementation, suggesting that valine is an EAA for Nile tilapia whereby the juveniles are able to assimilate the valine crystal for growth.…”
Section: Discussionsupporting
confidence: 92%
“…Also, the leucine and isoleucine contents of fish muscle were not affected by the varying the concentrations of dietary valine, similar to feeding trials with fingerling catla (Zehra & Khan, ), indicating the absence of antagonism among the branched‐chain amino acids in fish fed diets containing variable levels of valine. In addition, the moisture, lipid and ash contents of sampled juveniles showed no change in relation to dietary valine level, similar to the data reported for blunt snout bream (Ren et al., ). However, whole‐body lipid composition was observed to decrease with dietary valine supplementation in red sea bream (Rahimnejad & Lee, ) and Jian carp (Dong et al., ), whereas an increase in lipid content was recorded for mrigal carp (Abidi & Khan, ); the mechanisms of these differences need to be determined in further studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations